The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
DOI: 10.11606/d.25.2005.tde-17082005-143419
|View full text |Cite
|
Sign up to set email alerts
|

Influência da mecânica intrusiva de acentuação e reversão da curva de Spee, no grau de reabsorção radicular

Abstract: BAURU 2005 A DEUS, pela presença em cada momento da minha vida, pela luz que ilumina o meu caminho, por me abençoar, preservando minha saúde física e mental e me fortalecer diante dos momentos difíceis. DEDICO ESTE TRABALHO Aos meus pais, Geraldo e Maria José, pelo amor e dedicação sempre presentes durante a minha vida, por nunca medirem esforços para a minha formação, pelo apoio e incentivo constantes na busca dos meus ideais e na realização dos meus sonhos. À minha irmã, Karen, pelo carinho e atenção de semp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
3
0
2
Order By: Relevance
“…The periapical radiographs were analyzed as follows: The degree of initial and final, based on the classification proposed by Malmgren: Grade 0 (no resorption), grade 1 (presence of apical irregularities), grade 2 (presence of resorption by 2 mm), grade 3 (presence of resorption between 2 mm and a third of the original length), grade 4 (the presence of root resorption greater than one third of the original length of the root) ( Fig 1). 7,8 The bone crest was classified based on the observation of periapical radiographs as follows: Flat (width greater than 1 mm, representing the crest of a rectangular shape) and sharp (width less than or equal to 1 mm, representing the crest of triangular shape) ( Fig 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The periapical radiographs were analyzed as follows: The degree of initial and final, based on the classification proposed by Malmgren: Grade 0 (no resorption), grade 1 (presence of apical irregularities), grade 2 (presence of resorption by 2 mm), grade 3 (presence of resorption between 2 mm and a third of the original length), grade 4 (the presence of root resorption greater than one third of the original length of the root) ( Fig 1). 7,8 The bone crest was classified based on the observation of periapical radiographs as follows: Flat (width greater than 1 mm, representing the crest of a rectangular shape) and sharp (width less than or equal to 1 mm, representing the crest of triangular shape) ( Fig 2).…”
Section: Methodsmentioning
confidence: 99%
“…Incisors are the more constantly moved, for example, during retraction and intrusion. 8,12,22 Moreover, incisors are single-rooted elements and easier for obtaining images without distortion or image overlays. 15,18,23,33 The most common radiographic examination used for the detection of resorption is periapical xray.…”
Section: Methodsmentioning
confidence: 99%
“…The results of studies by Chiqueto et al 6 (2005) revealed a higher degree of root resorption with the use of intrusive mechanisms. Real intrusion is generally difficult to be obtained.…”
Section: Introductionmentioning
confidence: 95%
“…Esta metodologia também foi usada por Neves (1998) O método que classifica a reabsorção por escores proposto por Malmgren et al (1982) foi o mais indicado para este estudo; mesmo subjetivo, é utilizado com freqüência por diversos autores como Arnesen (1984), Beck e Harris (1994), Chiqueto (2005), no estudo da reabsorção radicular subseqüente ao tratamento ortodôntico, apresentando como principal vantagem o fato de não depender da padronização da radiografia inicial.…”
Section: Discussionunclassified